The world's worst children eaudiobook - Walliams, David (Nudged Children's Audiobooks, 2016)
Are you ready to meet the World's Worst Children? Five beastly boys and five gruesome girls! Meet TV super-fan, Sofia Sofa, so stuck to the sofa that she's turning into one; Dribbling Drew, a boy whose drool gets him into trouble; and not forgetting Blubbering Bertha, a girl who bawls and tells terrible tales. Also featuring a special appearance from everyone's favourite character: Raj!